Membaca Bekisar Merah, Mengeksplorasi Nilai-nilai Budaya Jawa - Sri Mariati (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2006)
Abstract This article is aimed at analyzing the reflection of Javanese cultural value which is expressed in Bekisar Merah by Ahmad Tohari. The analysis employs sociology of literature paradigm with mimetic approach. The result of the analysis shows that culture value and Javanese tradition emerge dominantly in the novel. Furthermore, it also demonstrates Javanese reflection of life, their religious value, and the supremacy of their negative presumption. The concept and character of Javanese attitude is implemented on the manner of the main character or the novel. This concept, named Hastasila, constitutes Trisila (remember, believe, and “mituhu”), and Pancasila (consent, acquiescent to one’s fate, wholeheartedly, patient, sensible). Key words: sociology of literature Javanese reflection of life, Hastasila, Trisila, Pancasila